A second-order extension of a robust implicit–explicit acoustic-transport splitting scheme for two-phase flows. (15th August 2022) - Tallois, Lucas; Peluchon, Simon; Villedieu, Philippe
Abstract: Diffuse interface methods have proven their ability to simulate complex two-phase flows. A number of robust numerical schemes have been developed to simulate such flows involving large density and pressure ratios. Diffusion induced by these methods, however, makes it difficult to localize the interface between the two fluids. To overcome this issue, while retaining the advantages of diffuse interface methods, a second-order extension using a Monotonic Upstream-centered Scheme for Conservation Laws-type (MUSCL-type) method of the implicit–explicit acoustic-transport splitting scheme introduced in Peluchon et al. (2017) is presented. A specific compressive limiter is used for the volume fraction in order to limit the diffusion of the interface between the two fluids. Numerical simulations are presented to illustrate the capability of the proposed new method to simulate highly complex compressible two-phase flows. Highlights: The design of a new limiter that control compressive character for the volume fraction. A more accurate implicit–explicit time scheme for the acoustic-transport splitting strategy. An algorithm to resolve the second-order in space scheme regarding the implicit time scheme. A robust second-order implicit–explicit scheme able to cope with liquid–gas configurations.